Responses of a drought-stressed pasture grass to silicon supplementation, fungal endophytes and simulated grazing - Scott N. Johnson; Rebecca K. Vandegeer; David T. Tissue; Susan E. Hartley; Ximena Cibils-Stewart (Agriculture, Ecosystems & Environment, 2026)

Contrasting Drought Thresholds Between Natural and Planted Forests on the Tibetan Plateau: Implications for Adaptive Plantation Transformation - Ting Li; David T. Tissue; Muzi Li (Global Change Biology, 2026)
Climate‐induced drought is a major threat to forest growth and ecosystem stability. However, the long‐term effects of drought on tree growth, especially across forests with contrasting stand structures, remain poorly understood. Based on 136,988 live tree records monitored from 1979 to 2017 in the southeastern Tibetan Plateau, we assessed how drought intensity, species richness, tree density, and stand age influence long‐term forest growth responses in natural and plantation forests. Plantation forests experienced more intense drought and showed lower drought tolerance thresholds (Palmer Drought Severity Index (PDSI) = −1.65) than natural forests (PDSI = −2.50). Species richness improved drought resistance under prolonged drought, yet suppressed growth in highly diverse natural forests. In plantations, moderate diversity levels (richness = 3–5) best balance growth and resistance. Younger stands ( 1250 stems/ha) amplified negative density dependence, reducing growth, and drought resistance. This study integrates natural and plantation forests to propose a novel structural threshold framework for enhancing plantation drought resistance. It suggests that targeted thinning and enrichment planting to moderate diversity levels in young, dense plantations can enhance drought resistance without compromising productivity. Promoting near‐natural restoration in plantations may further strengthen key ecosystem services—such as carbon sequestration and water retention—under a changing climate.

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

Limited leaf thermal acclimation but higher tolerance in subtropical trees after 10-year translocation in Dinghushan biosphere reserve - Ting Wu; David T Tissue; Wei Su; Honglang Duan; Mark G. Tjoelker; Sachin G. Chavan; Shuyidan Zhou; Junfeng Yuan; Liang Fang; Mengxiao Yu; Shizhong Liu; Guowei Chu; et al. (Agricultural and Forest Meteorology, 2025)

Seasonal Variation of Phyllosphere Microbial Communities Under Warming - Chaotang Lei; Shu‐Yi‐Dan Zhou; David T. Tissue; Roy Neilson; Zhiyang Lie; Ting Wu; Xujun Liu; Chushu Meng; Xu Li; Dong Zhu; Juxiu Liu (Global Change Biology, 2025)
The phyllosphere is a complex microbial ecosystem residing on plant leaves, hosting microbes that influence plant growth and fitness. The phyllosphere is sensitive to temperature and moisture, so understanding its response to climate warming and variable moisture associated with changes in seasons is crucial for predicting ecosystem function. We conducted a 12‐year warming experiment in a sub‐tropical forest by transplanting a natural ecosystem from higher to lower elevations. We sampled phyllosphere microbial communities across wet and dry seasons for three consecutive years (years 10–12) to assess potential adaptation strategies to warming. Phyllosphere microbial community structure and diversity varied seasonally, with higher bacterial richness in the dry season; however, warming reduced bacterial richness across seasons. Co‐occurrence networks revealed stronger microbial interactions in the dry season, which exhibited reduced connectivity under warming. Community assembly was largely stochastic, with warming enhancing species turnover and dispersal. Notably, plant probiotics, enriched in the wetter season with greater environmental disturbances, played a key role in adaptation to seasonal changes and warming. Seasonal shifts in microbial function were observed: wet‐season bacteria were enriched in carbohydrate and energy metabolism, while dry‐season bacteria showed elevated sulfur metabolism, reflecting adaptive metabolic strategies to environmental conditions. Our study enhances the understanding of the seasonal patterns of phyllosphere microbial communities and the impact of climate warming, offering new insights into plant–microbial adaptation strategies in response to climate change.

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

The influence of plant traits on soil microbial communities varies between arid and mesic grasslands - Eleonora Egidi; Dylan Bristol; Kamrul Hassan; David Tissue; Ian J. Wright; Uffe N. Nielsen (Plant and Soil, 2025)
Background and aims Both soil properties and plant traits shape the diversity, composition and functions of plant-associated soil microbial communities. However, the relative influence of these factors is poorly understood, as are interactive effects between factors and the degree to which their influence varies among climate zones. Methods To address this gap, we compared the diversity and composition of soil microbial communities associated with co-occurring C 3 and C 4 grasses from arid and mesic environments, and plant traits influencing them. Results Climate emerged as the main determinant of plant traits and microbial community properties. Within each climatic region, above- and below-ground traits and soil properties differentially affected microbial community composition, and their relative influence varied among communities. In both mesic and arid environments aboveground traits related to quantity and quality of leaf litter (e.g., specific leaf area, leaf C content) and nutrient availability were the most influential variables for community composition. However, in arid regions, belowground traits (i.e., root tissue density and specific root area) significantly contributed to structure the eukaryotic community, supporting the role of roots as important driver of eukaryotic differentiation in constrained environments. Further, the presence of C 4 plants in the arid region resulted in higher relative abundance of ciliate protists and higher recruitment of potentially beneficial microbial community members from green algae mediated by drought adaptation traits (e.g. decreased abundance of fine roots). Conclusions Overall, our study revealed a differential response of microbial communities to environmental conditions, suggesting that soil microbial community composition is influenced by trade-offs between host adaptive traits across distinct climatic regions.

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Energy and fertigation consumption and economic viability of a light blocking film in greenhouse lettuce production - Jing He; Terry Lin; Weiguang Liang; Sachin Chavan; Subbu Sethuvenkatraman; Mark Goldsworthy; David Tissue; Zhong-Hua Chen (Journal of Cleaner Production, 2024)

Forest demography depends on stand structure, functional traits, and climate in the eastern region of the Qinghai-Tibet Plateau - Ting Li; Qi Wang; David T. Tissue; Ian J. Wright; Peng Luo; Changhong Lai; Yang Liu; Xiaodan Wang (Agricultural and Forest Meteorology, 2024)

Herb hydraulics: Variation and correlation for traits governing drought tolerance and efficiency of water transport - Ruike Huang; Nan Di; Benye Xi; Jinyan Yang; Jie Duan; Ximeng Li; Jinchao Feng; Brendan Choat; David Tissue (Science of The Total Environment, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

Long-term field translocation differentially affects arbuscular mycorrhizal and ectomycorrhizal trees in a sub-tropical forest - Ting Wu; David T Tissue; Wei Su; Xu Li; Shimin Yang; Xujun Liu; Yue Liu; Zhiyang Lie; Shuyidan Zhou; Ze Meng; Junhua Yan; Xuli Tang; et al. (Agricultural and Forest Meteorology, 2023)

Elevated [CO2] enhances soil respiration and AMF abundance in a semiarid peanut agroecosystem - Haydee E. Laza; Veronica Acosta-Martinez; Amanda Cano; Jeff Baker; James Mahan; Dennis Gitz; Yves Emendack; Lindsey Slaughter; Robert Lascano; David Tissue; Paxton Payton (Agriculture, Ecosystems & Environment, 2023)

Green-up and brown-down: Modelling grassland foliage phenology responses to soil moisture availability - Jinyan Yang; Belinda E. Medlyn; Craig V.M. Barton; Amber C. Churchill; Martin G. De Kauwe; Mingkai Jiang; Arjunan Krishnananthaselvan; David T. Tissue; Elise Pendall; Sally A. Power (Agricultural and Forest Meteorology, 2023)

Response of the plant core microbiome to Fusarium oxysporum infection and identification of the pathobiome - Zhiguang Qiu; Jay Prakash Verma; Hongwei Liu; Juntao Wang; Bruna D. Batista; Simranjit Kaur; Arthur Prudêncio de Araujo Pereira; Catriona A. Macdonald; Pankaj Trivedi; Tim Weaver; Warren C. Conaty; David T. Tissue; et al. (Environmental Microbiology, 2022)
Plant core microbiomes consist of persistent key members that provide critical host functions, but their assemblages can be interrupted by biotic and abiotic stresses. The pathobiome is comprised of dynamic microbial interactions in response to disease status of the host. Hence, identifying variation in the core microbiome and pathobiome can significantly advance our understanding of microbial–microbial interactions and consequences for disease progression and host functions. In this study, we combined glasshouse and field studies to analyse the soil and plant rhizosphere microbiome of cotton plants ( Gossypium hirsutum ) in the presence of a cotton‐specific fungal pathogen, Fusarium oxysporum f. sp. vasinfectum (FOV). We found that FOV directly and consistently altered the rhizosphere microbiome, but the biocontrol agents enabled microbial assemblages to resist pathogenic stress. Using co‐occurrence network analysis of the core microbiome, we identified the pathobiome comprised of the pathogen and key associate phylotypes in the cotton microbiome. Isolation and application of some negatively correlated pathobiome members provided protection against plant infection. Importantly, our field survey from multiple cotton fields validated the pattern and responses of core microbiomes under FOV infection. This study advances key understanding of core microbiome responses and existence of plant pathobiomes, which provides a novel framework to better manage plant diseases in agriculture and natural settings.

Warming drives sustained plant phosphorus demand in a humid tropical forest - Zhiyang Lie; Guoyi Zhou; Wenjuan Huang; Kohmei Kadowaki; David T. Tissue; Junhua Yan; Josep Peñuelas; Jordi Sardans; Yuelin Li; Shizhong Liu; Guowei Chu; Ze Meng; et al. (Global Change Biology, 2022)
Phosphorus (P) is often one of the most limiting nutrients in highly weathered soils of humid tropical forests and may regulate the responses of carbon (C) feedback to climate warming. However, the response of P to warming at the ecosystem level in tropical forests is not well understood because previous studies have not comprehensively assessed changes in multiple P processes associated with warming. Here, we detected changes in the ecosystem P cycle in response to a 7‐year continuous warming experiment by translocating model plant‐soil ecosystems across a 600‐m elevation gradient, equivalent to a temperature change of 2.1°C. We found that warming increased plant P content (55.4%) and decreased foliar N:P. Increased plant P content was supplied by multiple processes, including enhanced plant P resorption (9.7%), soil P mineralization (15.5% decrease in moderately available organic P), and dissolution (6.8% decrease in iron‐bound inorganic P), without changing litter P mineralization and leachate P. These findings suggest that warming sustained plant P demand by increasing the biological and geochemical controls of the plant‐soil P‐cycle, which has important implications for C fixation in P‐deficient and highly productive tropical forests in future warmer climates.

Increasing aridity will not offset CO 2 fertilization in fast‐growing eucalypts with access to deep soil water - Daniel Nadal‐Sala; Belinda E. Medlyn; Nadine K. Ruehr; Craig V. M. Barton; David S. Ellsworth; Carles Gracia; David T. Tissue; Mark G. Tjoelker; Santi Sabaté (Global Change Biology, 2021)
Rising atmospheric [CO 2 ] ( C a ) generally enhances tree growth if nutrients are not limiting. However, reduced water availability and elevated evaporative demand may offset such fertilization. Trees with access to deep soil water may be able to mitigate such stresses and respond more positively to C a . Here, we sought to evaluate how increased vapor pressure deficit and reduced precipitation are likely to modify the impact of elevated C a (e C a ) on tree productivity in an Australian Eucalyptus saligna Sm. plantation with access to deep soil water. We parameterized a forest growth simulation model (GOTILWA+) using data from two field experiments on E. saligna : a 2‐year whole‐tree chamber experiment with factorial C a (ambient =380, elevated =620 μmol mol −1 ) and watering treatments, and a 10‐year stand‐scale irrigation experiment. Model evaluation showed that GOTILWA+ can capture the responses of canopy C uptake to (1) rising vapor pressure deficit ( D ) under both C a treatments; (2) alterations in tree water uptake from shallow and deep soil layers during soil dry‐down; and (3) the impact of irrigation on tree growth. Simulations suggest that increasing C a up to 700 μmol mol −1 alone would result in a 33% increase in annual gross primary production (GPP) and a 62% increase in biomass over 10 years. However, a combined 48% increase in D and a 20% reduction in precipitation would halve these values. Our simulations identify high D conditions as a key limiting factor for GPP. They also suggest that rising C a will compensate for increasing aridity limitations in E. saligna trees with access to deep soil water under non‐nutrient limiting conditions, thereby reducing the negative impacts of global warming upon this eucalypt species. Simulation models not accounting for water sources available to deep‐rooting trees are likely to overestimate aridity impacts on forest productivity and C stocks.

Long‐term effects of 7‐year warming experiment in the field on leaf hydraulic and economic traits of subtropical tree species - Ting Wu; David T. Tissue; Xu Li; Shizhong Liu; Guowei Chu; Guoyi Zhou; Yuelin Li; Mianhai Zheng; Ze Meng; Juxiu Liu (Global Change Biology, 2020)
Rising temperature associated with climate change may have substantial impacts on forest tree functions. We conducted a 7‐year warming experiment in subtropical China by translocating important native forest tree species ( Machilas breviflora , Syzygium rehderianum , Schima superba and Itea chinensis ) from cooler high‐elevation sites (600 m) to 1–2°C warmer low‐elevation sites (300 and 30 m) to investigate warming effects on leaf hydraulic and economic traits. Here, we report data from the last 3 years (Years 5–7) of the experiment. Warming increased leaf hydraulic conductance of S. superba to meet the higher evaporative demand. M. breviflora (300 m), S. rehderianum , S. superba and I. chinensis (300 and 30 m) exhibited higher area‐based and mass‐based maximum photosynthetic rates ( A a and A m , respectively) related to increasing stomatal conductance ( g s ) and stomatal density in the wet season, which led to rapid growth; however, we observed decreased growth of M. breviflora at 30 m due to lower stomatal density and decreased A a in the wet season. Warming increased photosynthetic nitrogen‐use efficiency and photosynthetic phosphorus‐use efficiency, but reduced leaf dry mass per unit area due to lower leaf thickness, suggesting that these tree species allocated more resources into upregulating photosynthesis rather than into structural investment. Our findings highlight that there was trait variation in the capacity of trees to acclimate to warmer temperatures such that I. chinensis may benefit from warming, but S. superba may be negatively influenced by warming in future climates.

Effect of high light on canopy-level photosynthesis and leaf mesophyll ion flux in tomato - Mohammad Hossain Babla; David Thomas Tissue; Christopher Ian Cazzonelli; Zhong-Hua Chen (Planta, 2020)

Low phosphorus supply constrains plant responses to elevated CO 2 : A meta‐analysis - Mingkai Jiang; Silvia Caldararu; Haiyang Zhang; Katrin Fleischer; Kristine Y. Crous; Jinyan Yang; Martin G. De Kauwe; David S. Ellsworth; Peter B. Reich; David T. Tissue; Sönke Zaehle; Belinda E. Medlyn (Global Change Biology, 2020)
Phosphorus (P) is an essential macro‐nutrient required for plant metabolism and growth. Low P availability could potentially limit plant responses to elevated carbon dioxide (eCO 2 ), but consensus has yet to be reached on the extent of this limitation. Here, based on data from experiments that manipulated both CO 2 and P for young individuals of woody and non‐woody species, we present a meta‐analysis of P limitation impacts on plant growth, physiological, and morphological response to eCO 2 . We show that low P availability attenuated plant photosynthetic response to eCO 2 by approximately one‐quarter, leading to a reduced, but still positive photosynthetic response to eCO 2 compared to those under high P availability. Furthermore, low P limited plant aboveground, belowground, and total biomass responses to eCO 2 , by 14.7%, 14.3%, and 12.4%, respectively, equivalent to an approximate halving of the eCO 2 responses observed under high P availability. In comparison, low P availability did not significantly alter the eCO 2 ‐induced changes in plant tissue nutrient concentration, suggesting tissue nutrient flexibility is an important mechanism allowing biomass response to eCO 2 under low P availability. Low P significantly reduced the eCO 2 ‐induced increase in leaf area by 14.3%, mirroring the aboveground biomass response, but low P did not affect the eCO 2 ‐induced increase in root length. Woody plants exhibited stronger attenuation effect of low P on aboveground biomass response to eCO 2 than non‐woody plants, while plants with different mycorrhizal associations showed similar responses to low P and eCO 2 interaction. This meta‐analysis highlights crucial data gaps in capturing plant responses to eCO 2 and low P availability. Field‐based experiments with longer‐term exposure of both CO 2 and P manipulations are critically needed to provide ecosystem‐scale understanding. Taken together, our results provide a quantitative baseline to constrain model‐based hypotheses of plant responses to eCO 2 under P limitation, thereby improving projections of future global change impacts.

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

An extreme heatwave enhanced the xanthophyll de-epoxidation state in leaves of Eucalyptus trees grown in the field - Namraj Dhami; John E. Drake; Mark G. Tjoelker; David T. Tissue; Christopher I. Cazzonelli (Physiology and Molecular Biology of Plants, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Drought and phosphorus affect productivity of a mesic grassland via shifts in root traits of dominant species - Jeff Chieppa; Uffe N. Nielsen; David T. Tissue; Sally A. Power (Plant and Soil, 2019)

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

Flooding and prolonged drought have differential legacy impacts on soil nitrogen cycling, microbial communities and plant productivity - Linh T. T. Nguyen; Yui Osanai; Ian C. Anderson; Michael P. Bange; David T. Tissue; Brajesh K. Singh (Plant and Soil, 2018)

Dry mass production, allocation patterns and water use efficiency of two conifers with different water use strategies under elevated [CO2], warming and drought conditions - Honglang Duan; Guomin Huang; Shuangxi Zhou; David T. Tissue (European Journal of Forest Research, 2018)

Elevated CO 2 did not affect the hydrological balance of a mature native Eucalyptus woodland - Teresa E. Gimeno; Tim R. McVicar; Anthony P. O'Grady; David T. Tissue; David S. Ellsworth (Global Change Biology, 2018)
Elevated atmospheric CO 2 concentration (e C a ) might reduce forest water‐use, due to decreased transpiration, following partial stomatal closure, thus enhancing water‐use efficiency and productivity at low water availability. If evapotranspiration ( E t ) is reduced, it may subsequently increase soil water storage (Δ S ) or surface runoff ( R ) and drainage ( D g ), although these could be offset or even reversed by changes in vegetation structure, mainly increased leaf area index ( L ). To understand the effect of e C a in a water‐limited ecosystem, we tested whether 2 years of e C a (~40% increase) affected the hydrological partitioning in a mature water‐limited Eucalyptus woodland exposed to Free‐Air CO 2 Enrichment (FACE). This timeframe allowed us to evaluate whether physiological effects of e C a reduced stand water‐use irrespective of L , which was unaffected by e C a in this timeframe. We hypothesized that e C a would reduce tree‐canopy transpiration ( E tree ), but excess water from reduced E tree would be lost via increased soil evaporation and understory transpiration ( E floor ) with no increase in Δ S , R or D g . We computed E t , Δ S , R and D g from measurements of sapflow velocity, L , soil water content (θ), understory micrometeorology, throughfall and stemflow. We found that e C a did not affect E tree , E floor , Δ S or θ at any depth (to 4.5 m) over the experimental period. We closed the water balance for dry seasons with no differences in the partitioning to R and D g between C a levels. Soil temperature and θ were the main drivers of E floor while vapour pressure deficit‐controlled E tree , though e C a did not significantly affect any of these relationships. Our results suggest that in the short‐term, e C a does not significantly affect ecosystem water‐use at this site. We conclude that water‐savings under e C a mediated by either direct effects on plant transpiration or by indirect effects via changes in L or soil moisture availability are unlikely in water‐limited mature eucalypt woodlands.

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

Impacts of waterlogging on soil nitrification and ammonia-oxidizing communities in farming system - Linh T. T. Nguyen; Yui Osanai; Ian C. Anderson; Michael P. Bange; Michael Braunack; David T. Tissue; Brajesh K. Singh (Plant and Soil, 2018)

A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.

Plant-soil interactions and nutrient availability determine the impact of elevated CO2 and temperature on cotton productivity - Yui Osanai; David T. Tissue; Michael P. Bange; Ian C. Anderson; Michael V. Braunack; Brajesh K. Singh (Plant and Soil, 2017)

Water, nitrogen and phosphorus use efficiencies of four tree species in response to variable water and nutrient supply - Feike A. Dijkstra; Yolima Carrillo; Michael J. Aspinwall; Chelsea Maier; Alberto Canarini; Hero Tahaei; Brendan Choat; David T. Tissue (Plant and Soil, 2016)

An ecoclimatic framework for evaluating the resilience of vegetation to water deficit - Patrick J. Mitchell; Anthony P. O'Grady; Elizabeth A. Pinkard; Timothy J. Brodribb; Stefan K. Arndt; Chris J. Blackman; Remko A. Duursma; Rod J. Fensham; David W. Hilbert; Craig R. Nitschke; Jaymie Norris; Stephen H. Roxburgh; et al. (Global Change Biology, 2016)
The surge in global efforts to understand the causes and consequences of drought on forest ecosystems has tended to focus on specific impacts such as mortality. We propose an ecoclimatic framework that takes a broader view of the ecological relevance of water deficits, linking elements of exposure and resilience to cumulative impacts on a range of ecosystem processes. This ecoclimatic framework is underpinned by two hypotheses: (i) exposure to water deficit can be represented probabilistically and used to estimate exposure thresholds across different vegetation types or ecosystems; and (ii) the cumulative impact of a series of water deficit events is defined by attributes governing the resistance and recovery of the affected processes. We present case studies comprising Pinus edulis and Eucalyptus globulus , tree species with contrasting ecological strategies, which demonstrate how links between exposure and resilience can be examined within our proposed framework. These examples reveal how climatic thresholds can be defined along a continuum of vegetation functional responses to water deficit regimes. The strength of this framework lies in identifying climatic thresholds on vegetation function in the absence of more complete mechanistic understanding, thereby guiding the formulation, application and benchmarking of more detailed modelling.

Seasonal microbial and nutrient responses during a 5-year reduction in the daily temperature range of soil in a Chihuahuan Desert ecosystem - Natasja C. van Gestel; Nirmala Dhungana; David T. Tissue; John C. Zak (Oecologia, 2016)

Elevated temperature is more effective than elevated [CO 2 ] in exposing genotypic variation in Telopea speciosissima growth plasticity: implications for woody plant populations under climate change - Guomin Huang; Paul D. Rymer; Honglang Duan; Renee A. Smith; David T. Tissue (Global Change Biology, 2015)
Intraspecific variation in phenotypic plasticity is a critical determinant of plant species capacity to cope with climate change. A long‐standing hypothesis states that greater levels of environmental variability will select for genotypes with greater phenotypic plasticity. However, few studies have examined how genotypes of woody species originating from contrasting environments respond to multiple climate change factors. Here, we investigated the main and interactive effects of elevated [ CO 2 ] ( C E ) and elevated temperature ( T E ) on growth and physiology of Coastal (warmer, less variable temperature environment) and Upland (cooler, more variable temperature environment) genotypes of an Australian woody species Telopea speciosissima . Both genotypes were positively responsive to C E (35% and 29% increase in whole‐plant dry mass and leaf area, respectively), but only the Coastal genotype exhibited positive growth responses to T E . We found that the Coastal genotype exhibited greater growth response to T E (47% and 85% increase in whole‐plant dry mass and leaf area, respectively) when compared with the Upland genotype (no change in dry mass or leaf area). No intraspecific variation in physiological plasticity was detected under C E or T E , and the interactive effects of C E and T E on intraspecific variation in phenotypic plasticity were also largely absent. Overall, T E was a more effective climate factor than C E in exposing genotypic variation in our woody species. Our results contradict the paradigm that genotypes from more variable climates will exhibit greater phenotypic plasticity in future climate regimes.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Quantifying ecological memory in plant and ecosystem processes - Kiona Ogle; Jarrett J. Barber; Greg A. Barron‐Gafford; Lisa Patrick Bentley; Jessica M. Young; Travis E. Huxman; Michael E. Loik; David T. Tissue (Ecology Letters, 2015)
The role of time in ecology has a long history of investigation, but ecologists have largely restricted their attention to the influence of concurrent abiotic conditions on rates and magnitudes of important ecological processes. Recently, however, ecologists have improved their understanding of ecological processes by explicitly considering the effects of antecedent conditions. To broadly help in studying the role of time, we evaluate the length, temporal pattern, and strength of memory with respect to the influence of antecedent conditions on current ecological dynamics. We developed the stochastic antecedent modelling ( SAM ) framework as a flexible analytic approach for evaluating exogenous and endogenous process components of memory in a system of interest. We designed SAM to be useful in revealing novel insights promoting further study, illustrated in four examples with different degrees of complexity and varying time scales: stomatal conductance, soil respiration, ecosystem productivity, and tree growth. Models with antecedent effects explained an additional 18–28% of response variation compared to models without antecedent effects. Moreover, SAM also enabled identification of potential mechanisms that underlie components of memory, thus revealing temporal properties that are not apparent from traditional treatments of ecological time‐series data and facilitating new hypothesis generation and additional research.

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Soil microbial and nutrient responses to 7 years of seasonally altered precipitation in a Chihuahuan Desert grassland - Colin W. Bell; David T. Tissue; Michael E. Loik; Matthew D. Wallenstein; Veronica Acosta ‐ Martinez; Richard A. Erickson; John C. Zak (Global Change Biology, 2014)
Soil microbial communities in Chihuahuan Desert grasslands generally experience highly variable spatiotemporal rainfall patterns. Changes in precipitation regimes can affect belowground ecosystem processes such as decomposition and nutrient cycling by altering soil microbial community structure and function. The objective of this study was to determine if increased seasonal precipitation frequency and magnitude over a 7‐year period would generate a persistent shift in microbial community characteristics and soil nutrient availability. We supplemented natural rainfall with large events (one/winter and three/summer) to simulate increased precipitation based on climate model predictions for this region. We observed a 2‐year delay in microbial responses to supplemental precipitation treatments. In years 3–5, higher microbial biomass, arbuscular mycorrhizae abundance, and soil enzyme C and P acquisition activities were observed in the supplemental water plots even during extended drought periods. In years 5–7, available soil P was consistently lower in the watered plots compared to control plots. Shifts in soil P corresponded to higher fungal abundances, microbial C utilization activity, and soil pH . This study demonstrated that 25% shifts in seasonal rainfall can significantly influence soil microbial and nutrient properties, which in turn may have long‐term effects on nutrient cycling and plant P uptake in this desert grassland.

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Reductions in daily soil temperature variability increase soil microbial biomass C and decrease soil N availability in the C hihuahuan Desert: potential implications for ecosystem C and N fluxes - Natasja C. van Gestel; Dylan W. Schwilk; David T. Tissue; John C. Zak (Global Change Biology, 2011)
Maximum and minimum soil temperatures affect belowground processes. In the past 50 years in arid regions, measured reductions in the daily temperature range of air ( DTR air ) most likely generated similar reductions in the unmeasured daily temperature range of soil ( DTR soil ). However, the role of DTR soil in regulating microbial and plant processes has not been well described. We experimentally reduced DTR soil in the C hihuahuan Desert at Big Bend National Park over 3 years. We used shade cloth that effectively decreased DTR soil by decreasing daily maximum temperature and increasing nighttime minimum temperature. A reduction in DTR soil generated on average a twofold increase in soil microbial biomass carbon, a 42% increase in soil CO 2 efflux and a 16% reduction in soil NO 3 − –N availability; soil available NH 4 + –N was reduced by 18% in the third year only. Reductions in DTR soil increased soil moisture up to 15% a few days after a substantial rainfall. Increased soil moisture contributed to higher soil CO 2 efflux, but not microbial biomass carbon, which was significantly correlated with DTR soil . Net photosynthetic rates at saturating light ( A sat ) in L arrea tridentata were not affected by reductions in DTR soil over the 3 year period. Arid ecosystems may become greater sources of C to the atmosphere with reduced DTR soil , resulting in a positive feedback to rising global temperatures, if increased C loss is not eventually balanced by increased C uptake. Ultimately, ecosystem models of N and C fluxes will need to account for these temperature‐driven processes.

Maintenance of C sinks sustains enhanced C assimilation during long-term exposure to elevated [CO2] in Mojave Desert shrubs - Iker Aranjuelo; Allison L. Ebbets; R. Dave Evans; David T. Tissue; Salvador Nogués; Natasja van Gestel; Paxton Payton; Volker Ebbert; Williams W. Adams III; Robert S. Nowak; Stanley D. Smith (Oecologia, 2011)

Precipitation magnitude and timing differentially affect species richness and plant density in the sotol grassland of the Chihuahuan Desert - Traesha R. Robertson; John C. Zak; David T. Tissue (Oecologia, 2010)

Exposure to preindustrial, current and future atmospheric CO 2 and temperature differentially affects growth and photosynthesis in Eucalyptus - OULA GHANNOUM; NATHAN G. PHILLIPS; JANN P. CONROY; RENEE A. SMITH; RENEE D. ATTARD; ROSLYN WOODFIELD; BARRY A. LOGAN; JAMES D. LEWIS; DAVID T. TISSUE (Global Change Biology, 2010)
To investigate if Eucalyptus species have responded to industrial‐age climate change, and how they may respond to a future climate, we measured growth and physiology of fast‐ ( E. saligna ) and slow‐growing ( E. sideroxylon ) seedlings exposed to preindustrial (290), current (400) or projected (650 μL L −1 ) CO 2 concentration ([CO 2 ]) and to current or projected (current +4 °C) temperature. To evaluate maximum potential treatment responses, plants were grown with nonlimiting soil moisture. We found that: (1) E. sideroxylon responded more strongly to elevated [CO 2 ] than to elevated temperature, while E. saligna responded similarly to elevated [CO 2 ] and elevated temperature; (2) the transition from preindustrial to current [CO 2 ] did not enhance eucalypt plant growth under ambient temperature, despite enhancing photosynthesis; (3) the transition from current to future [CO 2 ] stimulated both photosynthesis and growth of eucalypts, independent of temperature; and (4) warming enhanced eucalypt growth, independent of future [CO 2 ], despite not affecting photosynthesis. These results suggest large potential carbon sequestration by eucalypts in a future world, and highlight the need to evaluate how future water availability may affect such responses.

Physiological responses of two contrasting desert plant species to precipitation variability are differentially regulated by soil moisture and nitrogen dynamics - LISA D. PATRICK; KIONA OGLE; COLIN W. BELL; JOHN ZAK; DAVID TISSUE (Global Change Biology, 2009)
Alterations in global and regional precipitation patterns are expected to affect plant and ecosystem productivity, especially in water‐limited ecosystems. This study examined the effects of natural and supplemental (25% increase) seasonal precipitation on a sotol grassland ecosystem in Big Bend National Park in the Chihuahuan Desert. Physiological responses – leaf photosynthesis at saturating light ( A sat ), stomatal conductance ( g s ), and leaf nitrogen [N] – of two species differing in their life form and physiological strategies ( Dasylirion leiophyllum , a C 3 shrub; Bouteloua curtipendula , a C 4 grass) were measured over 3 years (2004–2006) that differed greatly in their annual and seasonal precipitation patterns (2004: wet, 2005: average, 2006: dry). Precipitation inputs are likely to affect leaf‐level physiology through the direct effects of altered soil water and soil nitrogen. Thus, the effects of precipitation, watering treatment, soil moisture, and nitrogen were quantified via multivariate hierarchical Bayesian models that explicitly linked the leaf and soil responses. The two species differed in their physiological responses to precipitation and were differentially controlled by soil water vs. soil nitrogen. In the relatively deeply rooted C 3 shrub, D. leiophyllum, A sat was highest in moist periods and was primarily regulated by deep (16–30 cm) soil water. In the shallow‐rooted C 4 grass, B. curtipendula, A sat was only coupled to leaf [N], both of which increased in dry periods when soil [N] was highest. Supplemental watering during the wet year generally decreased A sat and leaf [N] in D. leiophyllum , perhaps due to nutrient limitation, and physiological responses in this species were influenced by the cumulative effects of 5 years of supplemental watering. Both species are common in this ecosystem and responded strongly, yet differently, to soil moisture and nitrogen, suggesting that changes in the timing and magnitude of precipitation may have consequences for plant carbon gain, with the potential to alter community composition.

Forest fine‐root production and nitrogen use under elevated CO 2 : contrasting responses in evergreen and deciduous trees explained by a common principle - OSKAR FRANKLIN; ROSS E. McMURTRIE; COLLEEN M. IVERSEN; KRISTINE Y. CROUS; ADRIEN C. FINZI; DAVID T. TISSUE; DAVID S. ELLSWORTH; RAM OREN; RICHARD J. NORBY (Global Change Biology, 2009)
Despite the importance of nitrogen (N) limitation of forest carbon (C) sequestration at rising atmospheric CO 2 concentration, the mechanisms responsible are not well understood. To elucidate the interactive effects of elevated CO 2 (eCO 2 ) and soil N availability on forest productivity and C allocation, we hypothesized that (1) trees maximize fitness by allocating N and C to maximize their net growth and (2) that N uptake is controlled by soil N availability and root exploration for soil N. We tested this model using data collected in Free‐Air CO 2 Enrichment sites dominated by evergreen ( Pinus taeda ; Duke Forest) and deciduous [ Liquidambar styraciflua ; Oak Ridge National Laboratory (ORNL)] trees. The model explained 80–95% of variation in productivity and N‐uptake data among eCO 2 , N fertilization and control treatments over 6 years. The model explains why fine‐root production increased, and why N uptake increased despite reduced soil N availability under eCO 2 at ORNL and Duke. In agreement with observations at other sites, the model predicts that soil N availability reduced below a critical level diminishes all eCO 2 responses. At Duke, a negative feedback between reduced soil N availability and N uptake prevented progressive reduction in soil N availability at eCO 2 . At ORNL, soil N availability progressively decreased because it did not trigger reductions in N uptake; N uptake was maintained at ORNL through a large increase in the production of fast turnover fine roots. This implies that species with fast root turnover could be more prone to progressive N limitation of carbon sequestration in woody biomass than species with slow root turnover, such as evergreens. However, longer term data are necessary for a thorough evaluation of this hypothesis. The success of the model suggests that the principle of maximization of net growth to control growth and allocation could serve as a basis for simplification and generalization of larger scale forest and ecosystem models, for example by removing the need to specify parameters for relative foliage/stem/root allocation.

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)

Photosynthesis and reflectance indices for rainforest species in ecosystems undergoing progression and retrogression along a soil fertility chronosequence in New Zealand - David Whitehead; Natalie T. Boelman; Matthew H. Turnbull; Kevin L. Griffin; David T. Tissue; Margaret M. Barbour; John E. Hunt; Sarah J. Richardson; Duane A. Peltzer (Oecologia, 2005)

Respiration characteristics in temperate rainforest tree species differ along a long-term soil-development chronosequence - Matthew H. Turnbull; David T. Tissue; Kevin L. Griffin; Sarah J. Richardson; Duane A. Peltzer; David Whitehead (Oecologia, 2005)

Precipitation pulses and carbon fluxes in semiarid and arid ecosystems - Travis E. Huxman; Keirith A. Snyder; David Tissue; A. Joshua Leffler; Kiona Ogle; William T. Pockman; Darren R. Sandquist; Daniel L. Potts; Susan Schwinning (Oecologia, 2004)

Response of total night‐time respiration to differences in total daily photosynthesis for leaves in a Quercus rubra L. canopy: implications for modelling canopy CO 2 exchange - David Whitehead; Kevin L. Griffin; Matthew H. Turnbull; David T. Tissue; Victor C. Engel; Kim J. Brown; William S.F. Schuster; Adrian S. Walcroft (Global Change Biology, 2004)
Measurements of photosynthesis and respiration were made on leaves in summer in a Quercus rubra L. canopy at approximately hourly intervals throughout 5 days and nights. Leaves were selected in the upper canopy in fully sunlit conditions (upper) and in the lower canopy (lower). In addition, leaves in the upper canopy were shaded (upper shaded) to decrease photosynthesis rates. The data were used to test the hypothesis that total night‐time respiration is dependent on total photosynthesis during the previous day and that the response is mediated through changes in storage in carbohydrate pools. Measurements were made on clear sunny days with similar solar irradiance and air temperature, except for the last day when temperature, especially at night, was lower than that for the previous days. Maximum rates of photosynthesis in the upper leaves (18.7 μmol m −2 s −1 ) were approximately four times higher than those in the lower leaves (4.3 μmol m −2 s −1 ) and maximum photosynthesis rates in the upper shaded leaves (8.0 μmol m −2 s −1 ) were about half those in the upper leaves. There was a strong linear relationship between total night‐time respiration and total photosynthesis during the previous day when rates of respiration were normalized to a fixed temperature of 20°C, removing the effects of temperature from this relationship. Measurements of specific leaf area, nitrogen and chlorophyll concentration and calculations of the maximum rate of carboxylation activity, V cmax , were not significantly different between upper and upper shaded leaves 5 days after the shading treatment was started. There were small, but significant decreases in the rate of apparent maximum electron transport at saturating irradiance, J max ( P> 0.05), and light use efficiency, ɛ ( P 2 exchange for the full growing season. Introducing respiration as a function of total photosynthesis on the previous day resulted in a decrease in growing season night‐time respiration by 23% compared with the value when respiration was held constant. This highlights the need for a process‐based approach linking respiration to photosynthesis when modelling long‐term carbon exchange in forest ecosystems.

The contribution of bryophytes to the carbon exchange for a temperate rainforest - Evan H. DeLucia; Matthew H. Turnbull; Adrian S. Walcroft; Kevin L. Griffin; David T. Tissue; David Glenny; Tony M. McSeveny; David Whitehead (Global Change Biology, 2003)
Bryophytes blanket the floor of temperate rainforests in New Zealand and may influence a number of important ecosystem processes, including carbon cycling. Their contribution to forest floor carbon exchange was determined in a mature, undisturbed podocarp‐broadleaved forest in New Zealand, dominated by 100–400‐year‐old rimu ( Dacrydium cupressimum ) trees. Eight species of mosses and 13 species of liverworts contributed to the 62% cover of the diverse forest floor community. The bryophyte community developed a relatively thin (depth 2 partial pressures (median 46.6 Pa immediately below the bryophyte canopy) relative to the surrounding air (median 37.6 Pa at 100 mm above the canopy). Light‐saturated rates of net CO 2 exchange from 14 microcosms collected from the forest floor were highly variable; the maximum rate of net uptake (bryophyte photosynthesis – whole‐plant respiration) per unit ground area at saturating irradiance was 1.9 μmol m −2 s −1 and in one microcosm, the net rate of CO 2 exchange was negative (respiration). CO 2 exchange for all microcosms was strongly dependent on water content. The average water content in the microcosms ranged from 1375% when fully saturated to 250% when air‐dried. Reduction in water content across this range resulted in an average decrease of 85% in net CO 2 uptake per unit ground area. The results from the microcosms were used in a model to estimate annual carbon exchange for the forest floor. This model incorporated hourly variability in average irradiance reaching the forest floor, water content of the bryophyte layer, and air and soil temperature. The annual net carbon uptake by forest floor bryophytes was 103 g m −2 , compared to annual carbon efflux from the forest floor (bryophyte and soil respiration) of −1010 g m −2 . To put this in perspective of the magnitude of the components of CO 2 exchange for the forest floor, the bryophyte layer reclaimed an amount of CO 2 equivalent to only about 10% of forest floor respiration (bryophyte plus soil) or ∼11% of soil respiration. The contribution of forest floor bryophytes to productivity in this temperate rainforest was much smaller than in boreal forests, possibly because of differences in species composition and environmental limitations to photosynthesis. Because of their close dependence on water table depth, the contribution of the bryophyte community to ecosystem CO 2 exchange may be highly responsive to rapid changes in climate.

Age at flowering differentially affects vegetative and reproductive responses of a determinate annual plant to elevated carbon dioxide - James D. Lewis; Xianzhong Wang; Kevin L. Griffin; David T. Tissue (Oecologia, 2003)

Analysis of the growth of rimu (Dacrydium cupressinum) in South Westland, New Zealand, using process-based simulation models - David Whitehead; Graeme M. Hall; Adrian S. Walcroft; Kim J. Brown; Joe J. Landsberg; David T. Tissue; Matthew H. Turnbull; Kevin L. Griffin; William S. Schuster; Fiona E. Carswell; Craig M. Trotter; Ian L. James; et al. (International Journal of Biometeorology, 2002)

Photosynthetic characteristics in canopies of Quercus rubra, Quercus prinus and Acer rubrum differ in response to soil water availability - Matthew H. Turnbull; David Whitehead; David T. Tissue; William S. Schuster; Kim J. Brown; Victor C. Engel; Kevin L. Griffin (Oecologia, 2002)

Comparative responses of model C3 and C4 plants to drought in low and elevated CO 2 - JoY. K. Ward; David T. Tissue; Richard B. Thomas; . And; BoyD. R. Strain (Global Change Biology, 1999)
Summary Interactive effects of CO 2 and water availability have been predicted to alter the competitive relationships between C3 and C4 species over geological and contemporary time scales. We tested the effects of drought and CO 2 partial pressures ( p CO 2 ) ranging from values of the Pleistocene to those predicted for the future on the physiology and growth of model C3 and C4 species. We grew co‐occurring Abutilon theophrasti (C3) and Amaranthus retroflexus (C4) in monoculture at 18 (Pleistocene), 27 (preindustrial), 35 (current), and 70 (future) Pa CO 2 under conditions of high light and nutrient availability. After 27 days of growth, water was withheld from randomly chosen plants of each species until visible wilting occurred. Under well‐watered conditions, low p CO 2 that occurred during the Pleistocene was highly limiting to C3 photosynthesis and growth, and C3 plants showed increased photosynthesis and growth with increasing p CO 2 between the Pleistocene and future CO 2 values. Well‐watered C4 plants exhibited increased photosynthesis in response to increasing p CO 2 , but total mass and leaf area were unaffected by p CO 2 . In response to drought, C3 plants dropped a large amount of leaf area and maintained relatively high leaf water potential in remaining leaves, whereas C4 plants retained greater leaf area, but at a lower leaf water potential. Furthermore, drought‐treated C3 plants grown at 18 Pa CO 2 retained relatively greater leaf area than C3 plants grown at higher p CO 2 and exhibited a delay in the reduction of stomatal conductance that may have occurred in response to severe carbon limitations. The C4 plants grown at 70 Pa CO 2 showed lower relative reductions in net photosynthesis by the end of the drought compared to plants at lower p CO 2 , indicating that CO 2 enrichment may alleviate drought effects in C4 plants. At the Pleistocene p CO 2 , C3 and C4 plants showed similar relative recovery from drought for leaf area and biomass production, whereas C4 plants showed higher recovery than C3 plants at current and elevated p CO 2 . Based on these model systems, we conclude that C3 species may not have been at a disadvantage relative to C4 species in response to low CO 2 and severe drought during the Pleistocene. Furthermore, C4 species may have an advantage over C3 species in response to increasing atmospheric CO 2 and more frequent and severe droughts.

The photosynthesis – leaf nitrogen relationship at ambient and elevated atmospheric carbon dioxide: a meta‐analysis - Andrew G. Peterson; J. Timothy Ball; YiqI. Luo; Christopher B. Field; Peter B. Reich; Peter S. Curtis; Kevin L. Griffin; Carla A. Gunderson; Richard J. Norby; David T. Tissue; Manfred Forstreuter; AnA. Rey; et al. (Global Change Biology, 1999)
Estimation of leaf photosynthetic rate ( A ) from leaf nitrogen content ( N ) is both conceptually and numerically important in models of plant, ecosystem, and biosphere responses to global change. The relationship between A and N has been studied extensively at ambient CO 2 but much less at elevated CO 2 . This study was designed to (i) assess whether the A–N relationship was more similar for species within than between community and vegetation types, and (ii) examine how growth at elevated CO 2 affects the A–N relationship. Data were obtained for 39 C3 species grown at ambient CO 2 and 10 C3 species grown at ambient and elevated CO 2 . A regression model was applied to each species as well as to species pooled within different community and vegetation types. Cluster analysis of the regression coefficients indicated that species measured at ambient CO 2 did not separate into distinct groups matching community or vegetation type. Instead, most community and vegetation types shared the same general parameter space for regression coefficients. Growth at elevated CO 2 increased photosynthetic nitrogen use efficiency for pines and deciduous trees. When species were pooled by vegetation type, the A–N relationship for deciduous trees expressed on a leaf‐mass basis was not altered by elevated CO 2 , while the intercept increased for pines. When regression coefficients were averaged to give mean responses for different vegetation types, elevated CO 2 increased the intercept and the slope for deciduous trees but increased only the intercept for pines. There were no statistical differences between the pines and deciduous trees for the effect of CO 2 . Generalizations about the effect of elevated CO 2 on the A–N relationship, and differences between pines and deciduous trees will be enhanced as more data become available.

Elevated carbon dioxide does not affect average canopy stomatal conductance of Pinus taeda L. - Diane E. Pataki; Ram Oren; David T. Tissue (Oecologia, 1998)